Empagliflozin improves kidney outcomes in patients with or without heart Failure - Butler, Javed; Zannad, Faiez; Fitchett, David; Zinman, Bernard; Koitka-Weber, Audrey; Eynatten, Maximilian von; Zwiener, Isabella; George, Jyothis; Brückmann, Martina; Cheung, Alfred K.; Wanner, Christoph (Circulation. Heart failure, 2019)
Background: In EMPA-REG OUTCOME (Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients) empagliflozin significantly reduced the risk of cardiovascular and kidney out...